2020
DOI: 10.34172/ijhpm.2020.40
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Battle for Universal Pharmacare in Canada Comment on "Universal Pharmacare in Canada"

Abstract: Drug coverage in Canada is a patchwork; an inequitable inefficient and unsustainable patchwork with no coherence or purpose. Some people think that we can solve the problem by adding more patches, but the core of the problem is that it is a patchwork. For the working population, access to medicines is still organized as privileges offered by employers to their employees. Universal pharmacare would not only provide better access to needed prescription drugs, but also eliminate waste, ensure value-for-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…A number of recent studies have attempted to quantify the potential savings that a single-payer pharmacare program would provide Canada [ 38 – 43 ]. Published studies have indicated that a single-payer system could generate between $4 billion and $11 billion in annual savings for Canada [ 42 – 44 ].…”
Section: Pharmacare Economic Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of recent studies have attempted to quantify the potential savings that a single-payer pharmacare program would provide Canada [ 38 – 43 ]. Published studies have indicated that a single-payer system could generate between $4 billion and $11 billion in annual savings for Canada [ 42 – 44 ].…”
Section: Pharmacare Economic Considerationsmentioning
confidence: 99%
“…A number of proposals arguing for the enactment of particular policy frameworks for universal pharmacare, put forward by various sources in recent years, have enabled some political traction on the issue [ 38 – 43 ]. Five of the most recent pharmacare simulation models, with their associated cost reduction estimates, are briefly summarised in Table 2 .…”
Section: Pharmacare Economic Considerationsmentioning
confidence: 99%
See 3 more Smart Citations